2018
DOI: 10.1103/physreve.98.013305
|View full text |Cite
|
Sign up to set email alerts
|

Color-gradient lattice Boltzmann model with nonorthogonal central moments: Hydrodynamic melt-jet breakup simulations

Abstract: We develop a lattice Boltzmann (LB) model for immiscible two-phase flow simulations with central moments (CMs). This successfully combines a three-dimensional nonorthogonal CM-based LB scheme [De Rosis, Phys. Rev. E 95, 013310 (2017)2470-004510.1103/PhysRevE.95.013310] with our previous color-gradient LB model [Saito, Abe, and Koyama, Phys. Rev. E 96, 013317 (2017)2470-004510.1103/PhysRevE.96.013317]. Hydrodynamic melt-jet breakup simulations show that the proposed model is significantly more stable, even for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 93 publications
(191 reference statements)
1
28
0
Order By: Relevance
“…This is totally consistent with the BGK counterpart, where equilibrium populations just account for an extra magnetic field-dependent term [40]. Moreover, a third-order velocity term has been added to the equilibrium to simulate jet breakup [41] and, again, it is found that it does not affect the algorithmic procedure. In principle, it is possible to derive a central-momentsbased procedure for whatever arbitrary truncation order of the equilibrium populations.…”
Section: Introductionsupporting
confidence: 76%
“…This is totally consistent with the BGK counterpart, where equilibrium populations just account for an extra magnetic field-dependent term [40]. Moreover, a third-order velocity term has been added to the equilibrium to simulate jet breakup [41] and, again, it is found that it does not affect the algorithmic procedure. In principle, it is possible to derive a central-momentsbased procedure for whatever arbitrary truncation order of the equilibrium populations.…”
Section: Introductionsupporting
confidence: 76%
“…While the original formulation of LBM using explicit time stepping with local spatial interactions (thus, devoid of global solves) had been recognized in graphics as highly parallelizable [18]- [21], it quickly fell into disuse due to its substandard visual results and its limited stability and/or accuracy with respect to density ratios and Reynolds numbers. Yet, LBM has experienced a series of developments in recent years [22]- [24], especially with the development of central-moment relaxation models and coupling with Shan-Chen, free energy, or phase-field models [25]. As a result, modern Fig.…”
Section: Introductionmentioning
confidence: 99%
“…During the last three decades, the mesoscopic lattice Boltzmann method (LBM), based on the kinetic theory, has become an increasingly important method for numerical simulations of multiphase flows, mainly on account of its meso-scale features, easy implementation, and computational efficiency. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Generally, the existing multiphase LB models can be classified into four categories: the color-gradient model, 20,21 the pseudopotential model, 3,22 the free-energy model, 23,24 and the mean-field model. 25 Among them, the pseudopotential model is considered in the present work due to its simplicity and computational efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 In addition, the cascaded lattice Boltzmann method (CLBM), which employs moments in a co-moving frame in contrast to the stationary moments in MRT, has also been shown to improve numerical stability significantly compared with the classical SRT-LBM. 7,12,16,[37][38][39] The present work focuses on the MRT-LBM, in which the collision step is carried out in a (raw) moment space via a transformation matrix M, where different moments can be relaxed independently. The post-collision moments are then transformed back via M −1 , and the streaming step is implemented in the discrete velocity space as usual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation